2022
DOI: 10.1007/s11947-022-02881-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heating on Protein Denaturation, Water State, Microstructure, and Textural Properties of Antarctic Krill (Euphausia superba) Meat

Abstract: Antarctic krill (Euphausia superba) is an important source of biomass and high-quality protein. However, heat treatment of Antarctic krill negatively impacts its quality and compromises its utilization in the food industry. This study aimed to investigate the mechanisms underlying changes in Antarctic krill meat characteristics and physicochemical properties treated at different temperatures and holding times.Findings indicate that at higher temperatures and holding times, hardness and cooking loss of Antarcti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…However, when the proton had more freedom, it was easier to release the water. Thus, the relaxation time T 2 can be used to understand the migration law of water during the different processing methods of duck jerky, reflecting the dynamic properties of water, such as diffusion and state ( 24 ). The different processing methods had a highly significant effect on the transverse relaxation time T 2 of duck jerky ( p < 0.01) ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the proton had more freedom, it was easier to release the water. Thus, the relaxation time T 2 can be used to understand the migration law of water during the different processing methods of duck jerky, reflecting the dynamic properties of water, such as diffusion and state ( 24 ). The different processing methods had a highly significant effect on the transverse relaxation time T 2 of duck jerky ( p < 0.01) ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…However, those of the baked duck jerky appeared loose with significant gaps because the high temperatures during the prolonged baking and heating process caused the myofibril structure to lose its integrity and the myofascicles to contract, destroying its compact structure. It was previously reported that heating causes denaturation of myosin and the proteins that make up the myofibril membrane, which reduces the binding force of myogenic fibers to water and increases myofibril contraction, leading to the destruction of the myogenic fiber structure ( 24 ). Preboiling increased the contraction level in duck muscle fibers, resulting in irregularly textured muscle cross-sections.…”
Section: Resultsmentioning
confidence: 99%
“…Myo brillar protein (MP) is a decisive factor of sea bass in terms of avor, texture, and sensory properties, which accounts for 55% − 60% of the total muscle proteins, including myosin, actin, protomyosin and troponin (Han et al, 2022). MP is responsible for the functional properties of meat and its derivatives, such as emulsi cation, gel formation, and water retention capacity (Lin et al, 2023;. Due to various factors, MP generally exhibits limited dispersion and poor functional characteristics (Xu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The best method is heat sterilization, but this process can lead to food browning (color changes), damage the avor, and reduce nutritional value (Muñoz et al 2022).Canned Antarctic krill is one of the products exported to earn foreign exchange; however, its processing causes severe moisture loss, resulting in a tough texture, rough taste, and poor product quality. The main reason is that during the storage of raw Antarctic krill, the autolysis enzymes degrade the myo brillar protein, whereas it forms corrugated folded structures during thermal processing (Sun et al 2022). Consequently, improving the taste, avor, and nutritional value of canned Antarctic krill is a practical issue that needs to be addressed urgently.Phosphates are often used in the processing of aquatic products to improve product quality and reduce the loss of water, avor, and nutrients (Omar et al 2016).…”
mentioning
confidence: 99%
“…Canned Antarctic krill is one of the products exported to earn foreign exchange; however, its processing causes severe moisture loss, resulting in a tough texture, rough taste, and poor product quality. The main reason is that during the storage of raw Antarctic krill, the autolysis enzymes degrade the myo brillar protein, whereas it forms corrugated folded structures during thermal processing (Sun et al 2022). Consequently, improving the taste, avor, and nutritional value of canned Antarctic krill is a practical issue that needs to be addressed urgently.…”
mentioning
confidence: 99%